EFFECTS OF OUTDOOR STUDY ON STUDENTS’ COGNITIVE LEARNING OUTCOMES AND COOPERATION IN SCIENCE SUBJECTS - Edyyanto, Rohmat; Hastuti, Woro Sri (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2021)
This study aims to improve the cognitive learning outcomes and the cooperation in science subjects during the 2018/2019 school year by utilizing an outdoor study method. Fourth-graders in SD N 1 Pengasih were used as the subjects in this Classroom Action Class study. The models used were that of Kemmis and McTaggart, which include three stages, namely Planning, Implementation, and Observation, as well as Reflection. Meanwhile, the data retrieval instruments used were Observation sheets, questionnaires, and test questions. Quantitative and qualitative methods were used to analyze the collected data. In action cycles I and II, the number of students who scored in the good or excellent category amounted to 47% and 94%, while the average achievement of indicator cooperation was 69% and 80%. The cognitive learning outcomes of science subjects students to reach the Minimum Mastery Criteria (KKM) were 59% and 82% for action cycles I and II, respectively.